2018
DOI: 10.1038/s41467-018-02942-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide meta-analysis identifies five new susceptibility loci for pancreatic cancer

Abstract: In 2020, 146,063 deaths due to pancreatic cancer are estimated to occur in Europe and the United States combined. To identify common susceptibility alleles, we performed the largest pancreatic cancer GWAS to date, including 9040 patients and 12,496 controls of European ancestry from the Pancreatic Cancer Cohort Consortium (PanScan) and the Pancreatic Cancer Case-Control Consortium (PanC4). Here, we find significant evidence of a novel association at rs78417682 (7p12/ TNS3 , P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
153
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(162 citation statements)
references
References 68 publications
6
153
2
1
Order By: Relevance
“…Consequently, the binding motif of Hnf4g is the most significantly enriched transcription factor motif in the promoters of genes that are specifically upregulated in those tumor cells that lack a CSC phenotype ( Fig EV4B). This suggests that Hnf4g is playing a role in gene regulation even in transformed cancer cells, which is in line with recent reports on other cancer types, which revealed that dysregulated Hnf4g is associated with pancreatic (Klein et al, 2018), prostate (Shukla et al, 2017), and lung cancer (Wang et al, 2018). Overall, these observations illustrate the importance of system-wide interrogation and the power of integrative analyses to uncover novel biology related to intestinal homeostasis.…”
Section: Hnf4g Drives Enterocyte Differentiationsupporting
confidence: 89%
“…Consequently, the binding motif of Hnf4g is the most significantly enriched transcription factor motif in the promoters of genes that are specifically upregulated in those tumor cells that lack a CSC phenotype ( Fig EV4B). This suggests that Hnf4g is playing a role in gene regulation even in transformed cancer cells, which is in line with recent reports on other cancer types, which revealed that dysregulated Hnf4g is associated with pancreatic (Klein et al, 2018), prostate (Shukla et al, 2017), and lung cancer (Wang et al, 2018). Overall, these observations illustrate the importance of system-wide interrogation and the power of integrative analyses to uncover novel biology related to intestinal homeostasis.…”
Section: Hnf4g Drives Enterocyte Differentiationsupporting
confidence: 89%
“…In contrast with a mean OR of 1.20 per PDAC susceptibility allele reported in Caucasian GWAS to date, 19 we provide evidence of substantially higher per-allele risk estimates (dominant model) for rs11571833 and rs17879961 (OR = 1.78 and OR = 1.74, respectively). In contrast with a mean OR of 1.20 per PDAC susceptibility allele reported in Caucasian GWAS to date, 19 we provide evidence of substantially higher per-allele risk estimates (dominant model) for rs11571833 and rs17879961 (OR = 1.78 and OR = 1.74, respectively).…”
Section: Discussioncontrasting
confidence: 96%
“…This is the only well-powered study evaluating the effect of rare germline truncating BRCA2 rs11571833 (K3326X) and pathogenic CHEK2 rs17879961 (I157T) mutations in sporadic PDAC susceptibility until now. In contrast with a mean OR of 1.20 per PDAC susceptibility allele reported in Caucasian GWAS to date, 19 we provide evidence of substantially higher per-allele risk estimates (dominant model) for rs11571833 and rs17879961 (OR = 1.78 and OR = 1.74, respectively). This further backs the well known "common-disease rare-variant hypothesis" that argues that rare variants act as primary drivers and major contributors to common diseases.…”
Section: Discussioncontrasting
confidence: 96%
“…Recently, investigations have reported a number of genetic factors or susceptibility genes or loci for PanC risk. PanC high‐penetrance genes include BRCA1 , BRCA2 , TP53 , CDKN2A , APC , STK11 and MMR genes, whereas low‐penetrance risk loci include chromosome 9q34 (in the ABO blood group gene), 1q32.1 (in NR5A2 ), 5p15.33 (in the CLPTM1L ‐ TERT gene region), 16q23.1 ( BCAR1 ), 13q12.2 ( PDX1 ), 22q12.1 ( ZNRF3 ), 1p36.33 ( NOC2L ), and 22q13.1 ( PDGFB ) . However, these established genes or loci could explain only 20%‐30% of PanC risk, including 5%‐10% of the familial aggregation of PanC.…”
Section: Introductionmentioning
confidence: 99%
“…PanC high-penetrance genes include BRCA1, BRCA2, TP53, CDKN2A, APC, STK11 and MMR genes, whereas low-penetrance risk loci include chromosome 9q34 (in the ABO blood group gene), 1q32.1 (in NR5A2), 5p15.33 (in the CLPTM1L-TERT gene region), 16q23.1 (BCAR1), 13q12.2 (PDX1), 22q12.1 (ZNRF3), 1p36.33 (NOC2L), and 22q13.1 (PDGFB). [7][8][9][10][11] However, these established genes or loci could explain only 20%-30% of PanC risk, including 5%-10% of the familial aggregation of PanC. In the remaining 80%-85% of sporadic patients, there has been limited success in resolving the genetic architecture of PanC.…”
Section: Introductionmentioning
confidence: 99%